Yemen : Early Childhood Development 2013 - World Bank (Washington, DC, 2015)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies that affect young children in Yemen. This report is part of a series of reports prepared by the World Bank using the SABER-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Yemen, along with regional and international comparisons.